Evaluating the impact of sprouting conditions on the glucosinolate content of Brassica oleracea sprouts. (July 2015) - Vale, A.P.; Santos, J.; Brito, N.V.; Fernandes, D.; Rosa, E.; Oliveira, M. Beatriz P.P.
Graphical abstract: Brassica sprouts had a higher content of aliphatic glucosinolates than indole glucosinolates, being sinigrin, glucoiberin, glucoraphanin and progoitrin the major compounds in the sprouts. Highlights: All sprouts had higher content of aliphatic glucosinolates than indole glucosinolates. Galega kale sprouts had the higher glucosinolate content and myrosinase activity. Sinigrin, glucoiberin, glucoraphanin and progoitrin were the major compounds found. Light exposure and short sprouting phase potentiate sprouts glucosinolate content. Abstract: The glucosinolates content of brassica plants is a distinctive characteristic, representing a healthy advantage as many of these compounds are associated to antioxidant and anti-carcinogenic properties. Brassica sprouts are still an underutilized source of these bioactive compounds. In this work, four varieties of brassica sprouts (red cabbage, broccoli, Galega kale and Penca cabbage), including two local varieties from the North of Portugal, were grown to evaluate the glucosinolate profile and myrosinase activity during the sprouting. Also the influence of light/darkness exposure during sprouting on the glucosinolate content was assessed. Glucosinolate content and myrosinase activity of the sprouts was evaluated by HPLC methods. All sprouts revealed a higher content of aliphatic glucosinolates than of indole glucosinolates, contrary to the profile described for most of brassica mature plants. Galega kale sprouts had the highest glucosinolate content, mainly sinigrin and glucoiberin, which are recognized for their beneficial health effects. Penca cabbage sprouts were particularly richer in glucoraphanin, who was also one of the major compounds in broccoli sprouts. Red cabbage showed a higher content of progoitrin. Regarding myrosinase activity, Galega kale sprouts showed the highest values, revealing that the use of light/dark cycles and a sprouting phase of 7–9 days could be beneficial to preserve the glucosinolate content of this variety.